2010
DOI: 10.1590/s1807-59322010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Deep breathing heart rate variability is associated with respiratory muscle weakness in patients with chronic obstructive pulmonary disease

Abstract: BACKGROUNDA synchronism exists between the respiratory and cardiac cycles. However, the influence of the inspiratory muscle weakness in chronic obstructive pulmonary disease (COPD) on cardiac autonomic control is unknown. The purpose of the present investigation was to evaluate the influence of respiratory muscle strength on autonomic control in these patients.METHODSTen chronic obstructive pulmonary disease patients (69±9 years; FEV1/FVC 59±12% and FEV1 41±11% predicted) and nine age-matched healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 31 publications
1
45
0
4
Order By: Relevance
“…37 However, 3 studies reported comparable time-domain parameters between subjects with COPD and healthy controls. 36,39,41 The frequency-domain values for heart rate variability showed more variation across the studies. Lower frequencydomain values were reported in some studies for LF, 3 10,34,38,44 and HFnu in subjects with COPD compared with their healthy counterparts.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 94%
See 1 more Smart Citation
“…37 However, 3 studies reported comparable time-domain parameters between subjects with COPD and healthy controls. 36,39,41 The frequency-domain values for heart rate variability showed more variation across the studies. Lower frequencydomain values were reported in some studies for LF, 3 10,34,38,44 and HFnu in subjects with COPD compared with their healthy counterparts.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 94%
“…Fifteen studies of high methodological quality investigated the differences in heart rate variability values between subjects with COPD and healthy controls. 3,10,13,19,[34][35][36][37][38][39][40][41][42][43][44] Most of these studies reported significantly lower heart rate variability in subjects with COPD. Specifically, the time-domain parameters in most of the studies (12 of 15) showed that subjects with COPD had lower heart rate variability compared with healthy controls.…”
Section: Evidence For Autonomic Function In Subjectsmentioning
confidence: 99%
“…Reis (2010) исследуя пациентов с ХОБЛ и здоровых добровольцев, нашёл снижение RMSSD (18,3±15,6 мс) и SDNN (32,1±21,2 мс) при пато-логии бронхолёгочной системы в сравнении со здоровыми людьми (RMSSD 43,5±27,9 мс, SDNN 63,8±29,1 мс). В этой же работе при ХОБЛ отме-чено снижение высокочастотных (0,1±0,03 мс 2 ) и низкочастотных (0,9±0,03 мс 2 ) компонентов спек-тра [25].…”
Section: казанский медицинский журнал 2016 г том 97 №3unclassified
“…Reis et al (54) found that patients with COPD present impaired sympathetic-vagal balance at rest. Those authors also found that autonomic control of HR is associated with inspiratory muscle weakness in COPD.…”
Section: Copdmentioning
confidence: 99%